Turmeric (Curcuma longa L.) drying: an optimization approach using microwave-vacuum drying - Hirun,S. (Springer India, 2015)
© 2012, Association of Food Scientists & Technologists (India). This study investigated the effect of microwave power (2,400–4,000 W) and drying times (10–30 min) on the quality of dried turmeric in terms of colour (L, a*, b*), moisture content, water activity (aw), ash, antioxidant activity (2,2-dipheneyl-1-picrylhydrazyl; DPPH), total phenolic and curcuminoids content. In addition, Response Surface Methodology (RSM) was implemented to optimize the drying conditions for turmeric. A range of quality parameters, microwave power (W) and time (min) were fitted to quadratic models using a central composite design. The Analysis of Variance (ANOVA) statistic results suggested that the optimal qualities (i.e., aw, value, moisture content, phenolic content, curcuminoid content and EC50 and L value) of dried turmeric were achieved at high vacuum-microwave power (3,500–4,000 W) and long duration (27–30 min). The improvement in the quality of dried turmeric microwave-vacuum drying in these conditions was illustrated through the enzymatic browning reaction via inhibition of polyphenol oxidase which suppressed the formation of the brown pigments and increased the phenol substrates.